2011
DOI: 10.1016/j.chembiol.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

AAK1 Identified as an Inhibitor of Neuregulin-1/ErbB4-Dependent Neurotrophic Factor Signaling Using Integrative Chemical Genomics and Proteomics

Abstract: Summary Target identification remains a challenge for the field of chemical biology. We describe here an integrative chemical genomic and proteomic approach combining the use of differentially active analogs of small-molecule probes with stable isotope labeling by amino acids in cell culture (SILAC)-mediated affinity enrichment, followed by subsequent testing of candidate targets using RNA interference (RNAi)-mediated gene silencing. We applied this approach to characterizing the natural product K252a and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…How AAK1 function regulates dendrite morphogenesis remains to be investigated. Intriguingly, AAK1 was recently implicated in regulating various signaling pathways including Notch (Gupta-Rossi et al, 2011), ErbB4 (Kuai et al, 2011) and Drosophila Neuroglian (Yang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…How AAK1 function regulates dendrite morphogenesis remains to be investigated. Intriguingly, AAK1 was recently implicated in regulating various signaling pathways including Notch (Gupta-Rossi et al, 2011), ErbB4 (Kuai et al, 2011) and Drosophila Neuroglian (Yang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…We described an approach using stable isotope labeling by amino acids in cell culture (SILAC)-based quantitative proteomics and affinity matrices to quantitatively measure even small (~20%) changes in protein enrichment by SM probes over control pull-downs, allowing sensitive and specific identification of direct targets and higher-order interactors of SM probes from cell lysates 13, 14 . We applied our SILAC target ID approach to identify novel targets of immunophilin ligands 13 , natural products 15 , and kinase inhibitors 13, 1618 . Our SILAC target ID workflow applies mild non-ionic detergents, yielding bona fide targets with one milligram of input protein and allows the identification of lower affinity interactions (K d ~ 40 µM) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…An integrated approach was used to characterize the ability of a well-known natural product, K252a, to potentiate Nrg1-induced neurite outgrowth 141 . Integrating quantitative proteomic results with a lentivirus-mediated loss-of-function screen to validate candidate target proteins, the authors found that knockdown of AAK-1 reproducibly potentiated Nrg-1–driven neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%